Structural Model of Knowledge and Attitude Towards Testicular Self-Examination Behavior Among Adolescents - Namira Yusuf; Nisrina Hanum; Husna Husna; Ismail Ismail; Yuliani Safmila (Indonesian Journal of Global Health Research, 2026)
Adolescent reproductive health, particularly among males, remains a sensitive and rarely discussed issue. Testicular Self-Examination (TSE) is a simple and effective method for the early detection of testicular cancer; however, awareness and practice among adolescents are still very low, especially in Aceh. This study aimed to analyze the factors influencing knowledge, attitudes, and behavior regarding TSE among male adolescents. A quantitative cross-sectional study was conducted from July to August 2025 among 422 junior high school students aged 14–17 in Aceh, selected through a stratified random sampling method. Data were collected using validated and reliable questionnaires and analyzed with PLS-SEM. The results showed that age and access to TSE information significantly influenced knowledge and attitudes, while general reproductive health information had no significant effect. Knowledge and attitudes significantly predicted TSE behavior, explaining 58.8% of the variance. These findings highlight the need for schools to integrate reproductive health education through outreach programs, posters, and curriculum content to improve adolescent knowledge, foster positive attitudes, and encourage regular TSE practices for early detection of testicular cancer.